پارتیکڵ لە زمانى کوردى دا - قادر, ابوبکر عمر (Sulaimani Journal for Humanities, 2007)
This study is an attempt to show a grammatical word class (a grammatical category) which participates in forming noun phrases, verb phrases, and complementizer phrases within the scope of X-bar theory. This theory, which is an analytical one, describes and analyzes the grammatical structures of the constituents and the main constituents of sentences and phrases. In this study, the researcher has accounted for this word class (category) as a functional word in order to be distinguished from the lexical words (like nouns, adjectives, verbs, etc.) which would be the head within the X-bar theory. That is, the function word is the headword represented as X ; the extension of this unit X in X- is because of having a modifier.Then, X- is extended to X= by means of aspecifiers. Each of the specifiers and the modifiers has its own position in natural Languages. Some important factures of this word class are as follows : 1- Their forms do not change (or no change is in their form). 2- They are not conjugated further. 3- They do not participate in forming new words (they are not productive). 4- They are used in forming phrases and sentences. 5- In spite of participating in syntactic structures, they have semantic and pragmatics uses. The researcher has classified this word class, according to their position, in each of the noun phrases,verb phrases , and complementizer phrases.That is, the words which (كام) and what (ض) as question adjectivals are added in noun phrases, distributives,demonstative pronouns,quantifiers and numerals. In verb phrases, the researcher has also demonstrated, the words that have the role of modifiers precede the verbs.While in the complementizer structure of the compound sentences, the function words preceed the dependent clauses and they will be the head of the complementizer phrases, assuming the same role of prepositions in prepositional phrases. In comparison to the position of wh- word of question sentences and according to the view of this theory (X-bar theory) and the occurrence of the exclamatory particles at the beginning of the semtence, except with the exclamatory tone, the researcher has illustrated that these particles are specifers in forming exclamatory sentences, in ordere to show the types of the sentences in respect of concept and meaning.